PENYADARAN HUKUM DAN MENGEMBANGKAN PEREKONOMIAN SERTA LINGKUNGAN BERSIH MELALUI METODE EDUKASI DESA KALIPECABEAN KECAMATAN CANDI KABUPATEN SIDOARJO - Sanjaya, Soni; Oktafia, Fitri; Dara, Sandra (Jurnal ABDI Bhayangkara, 2022)
Legal awareness sometimes we called public legal education is the empowerment of individuals regarding issues involving the law. Legal awareness helps to promote consciousness of legal culture, participation in the formation of laws and the rule of law. But, unfortunately the understanding that is understood by the community is different from what should be created through legislation. Most people understand the wrong thing. Providing legal awareness in the community doesn’t only make the community the people who want to defend the law, but also get the correct information about how the law is. Activities are carried out through the Community Development Program (CDP) program which is a community service-based activity to increase student empathy for the condition of society and its environment. Bhayangkara University Surabaya Community Development Program (CDP) 2020 was held in Kalipecabean Village, Candi District, Sidoarjo Regency. College student have to mingle with the society, giving service to them. College student work in reality for the society. And within 1 (one) weeks we have to find an innovation that has long term impact for the society. with service methods such as counseling, and mentoring children tostudy and learn Al-Qur’an. The results show a positive response and high community participation including following legal awareness socialization activities, online buying and selling socialization, socialization of the dangers of disease during the rainy season